Geochemical characteristics of bitumen from the Cambrian reservoir in the Ordos basin, Northern China: Insights into bitumen classification and origin. (1st June 2022) - Huang, Junping; He, Wenxiang; Lin, Junfeng; Li, Xiangbo; Xu, Yaohui; Wang, Yating; Wang, Hongbo
Graphical abstract: Highlights: The bitumens from the Cambrian reservoir are genetically classified into three types. Neural network and cross-plot analyses are useful for determing origin of bitumens. The Type I and II bitumens are derived from the Lower Cambrian source rocks. Type III bitumen might originate from Changchengian source rocks. Abstract: The high mature to over-mature bitumen from the Cambrian reservoir in the Ordos basin, Northern China, is classified into three types (Type I, II, and III bitumens) and the sources of different types of bitumen are investigated using cluster, neural-network, and cross-plot analyses of major, trace elements and carbon isotopic composition. Type I bitumen is hosted in the fractures and pores of dolomite distributed in the southwestern part of the Ordos basin, and originates mainly from the Lower Cambrian source rocks containing abundant organic matter. Type II bitumen is hosted in the fractures of oolitic limestone distributed in the eastern and southeastern part of the Ordos basin, and also stems from the Lower Cambrian source rocks. Type III bitumen is hosted in the pores of sandstone distributed in the interior of the Ordos basin, might originate from Mesoproterozoic Changchengian source rocks. Cluster and neural-network analyses of major and trace elements are proved to be highly effective tools for determining different types and origin of reservoir bitumen. The study findings provide guidance in the exploration of hydrocarbons in the Palaeozoic and deeper strata of the Ordos basin and may contribute to further breakthroughs in deep hydrocarbon exploration.